A bis(mu-chlorido)-bridged cobalt(II) complex with silyl-containing schiff base as a catalyst precursor in the solvent-free oxidation of cyclohexane - Zaltariov, Mirela-Fernanda (2017)
A new bis(µ-chlorido)-bridged cobalt(II) complex [Co2(µ-Cl)2(HL2)4][CoCl4] (1), where HL2 is a silyl-containing Schiff base, was synthesised. The structure of this compound was established by X-ray crystallography revealing a zwitterionic form adopted by the organic ligand. The temperature dependence of the magnetic susceptibility and the field dependence of the magnetisation indicate the presence of ferromagnetic interactions between paramagnetic d7 cobalt(II) centres (SCo = 3/2). The exchange coupling parameter J(Co1–Co2) = +7.0 cm–1 extracted from broken-symmetry (BS) DFT calculations agrees well with the value of +8.8 cm–1 determined from the experimental data by fitting them with the Hamiltonian math formula. Electrochemical studies indicate that complex 1 is inefficient as a catalyst in electrochemical reduction of protons. One of the reasons is the low stability of the complex in solution. In contrast, 1 acts as an effective homogeneous (pre)catalyst in the microwave-assisted neat oxidation of cyclohexane with aqueous tBuOOH (TBHP). The possible mechanism of catalytic oxidation and other advantages of using 1 in the oxidation of cycloalkanes are discussed.